Understanding the global e-waste crisis - Gaghana, Regina Desire (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: The escalation of the global e-waste crisis presents profound environmental and public health concerns stemming from the inadequate management of discarded electrical and electronic devices. Methods: This paper provides an in-depth examination of the causative factors, ramifications, and potential remedial measures associated with this burgeoning issue. Findings: It delineates the impacts of rapid technological advancements, planned obsolescence strategies, and the dearth of public awareness on the exponential growth of e-waste. Furthermore, the paper elucidates solutions such as heightened public awareness campaigns, the implementation of remanufacturing protocols, and the enactment of regulatory frameworks mandating responsible disposal practices. Conclusiom: Emphasizing the imperative for enhanced e-waste management strategies, the paper advocates for concerted efforts across governmental, corporate, and societal domains to mitigate the adverse repercussions on both environmental sustainability and human well-being. Through rigorous interdisciplinary collaboration and proactive intervention, effective strategies can be formulated to alleviate the e-waste crisis and fortify global environmental resilience.